2016
DOI: 10.1016/j.jmoldx.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing-Assisted DNA-Based Digital PCR for a Personalized Approach to the Detection and Quantification of Residual Disease in Chronic Myeloid Leukemia Patients

Abstract: (200) 28Recent studies indicate that 40% of chronic myeloid leukaemia (CML) patients who achieve 29 sustained undetectable BCR-ABL1 transcripts on tyrosine kinase inhibitor (TKI) therapy 30 remain disease-free after drug discontinuation. In contrast, 60% experience return of 31 detectable disease and have to re-start treatment, thus highlighting the need for an improved 32 method of identifying patients with the lowest likelihood of relapse. Here we describe the 33 validation of a personalised DNA-based digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 43 publications
0
34
0
2
Order By: Relevance
“…In addition, we and others have compared the quantification of BCR-ABL in genomic DNA and RNA in serial samples and have shown that individual patients may have consistently higher or lower expression of BCR-ABL mRNA for a given number of CML cells. 47,48 This interindividual difference results in a measurement bias whereby RQ-PCR may underestimate the level of residual disease in some patients. Although genomic Q-PCR for BCR-ABL is not widely available, it is a promising research tool to elucidate the relationship between MRD and TFR outcome.…”
Section: Areas Of Future Investigationmentioning
confidence: 99%
“…In addition, we and others have compared the quantification of BCR-ABL in genomic DNA and RNA in serial samples and have shown that individual patients may have consistently higher or lower expression of BCR-ABL mRNA for a given number of CML cells. 47,48 This interindividual difference results in a measurement bias whereby RQ-PCR may underestimate the level of residual disease in some patients. Although genomic Q-PCR for BCR-ABL is not widely available, it is a promising research tool to elucidate the relationship between MRD and TFR outcome.…”
Section: Areas Of Future Investigationmentioning
confidence: 99%
“…Nextgeneration sequencing combined with digital DNA BCR-ABL1 PCR is a recent innovation that could be the most sensitive currently available technique. 41 In the future, this or other novel techniques may be used to revisit the relevance of the BCR-ABL1 detection limit for patient selection for TKI cessation studies. It is clear that currently available technology could be of immediate clinical benefit for monitoring the molecular response of many patients in low-resource regions or for laboratories that lack relevant molecular biology expertise for adequate BCR-ABL1 method development.…”
Section: Molecular Monitoring: How Low Do You Need To Go?mentioning
confidence: 99%
“…However, the observed ~0.2% fractional abundance was enabled, in part, by the addition of ~40,000 KRAS copies per reaction; this level of sensitivity may not always be achievable using in vivo extracts such as cfDNA from plasma, that typically yields ~500 copies/mL plasma (33). In addition to cancer models, other rare SNV models would also be applicable to this framework (14, 15) as well as simpler targets that do not require specific measurement of a given variant in the presence of the wt allele, such as quantification of specific pathogens or gene fusions (34, 35).…”
Section: Discussionmentioning
confidence: 99%